Magnitude of placebo response in clinical trials of paroxetine for vasomotor symptoms: a meta-analysis - Rhodes, Joshua R.; Alldredge, Cameron T.; Elkins, Gary R. (Frontiers in Psychiatry, 2023)
Vasomotor symptoms, or hot flashes, are among the most common complaints for menopausal and postmenopausal women. As an alternative to hormone replacement therapy, paroxetine mesylate became the only nonhormonal treatment approved by the U.S. Food and Drug Administration, despite limited evidence for its efficacy. This meta-analysis aims to determine the magnitude of placebo response across all clinical trials of paroxetine for VMS treatment. The primary outcomes evaluated were hot flash frequency and hot flash severity scores across six randomized clinical trials, including 1,486 women. Results indicate that 79% of the mean treatment response for hot flash frequency is accounted for by a placebo response, resulting in a mean true drug effect of 21% at most. Additionally, 68% of the mean treatment response for hot flash severity is accounted for by a placebo response, resulting in a maximum true drug effect of 32%. The healthcare and scientific implications of these findings are discussed.